Web-Based Psychoeducation Program for Caregivers of First-Episode of Psychosis: An Experience of Chinese Population in Hong Kong - Chan, Sherry K. W.; Tse, Samson; Sit, Harrison Long Tin; Hui, Christy L. M.; Lee, Edwin H. M.; Chang, Wing C.; Chen, Eric Y. H. (Frontiers in Psychology, 2016)
Caregivers of patients with first-episode psychosis are often with little knowledge about the illness and experience more burden of care. Psychoeducation to caregivers has shown to be effective in improving outcomes of patients and possibly reduce stress of the caregivers. This has been recommended as one of the key psychosocial interventions for specific early intervention for psychosis service. However, the accessibility of the service, high case load of the health care professionals and self-stigma of caregivers are often the barriers of implementation of these programs in the real world. Incorporating the convenience of information access via internet and the concept of self-management approach, an interactive internet-based self-help psychoeducation program (iPEP) (www.ipep.hk) for the caregivers of patients with psychosis was established targeting the caregivers of patients with psychosis at early stage in Hong Kong. It provides a comprehensive online resource center in both written and video format on knowledge about psychosis, skills of care and information of local resources. It also has a forum facilitate information exchange between healthcare professionals and the caregivers, allowing for self-management. Over 800 caregivers has joined the program as members. The evaluation of the subset of the members/users of the iPEP suggested that the iPEP program has been well received and appreciated by the caregivers of patients with FEP locally. It can potentially serve as a platform for future development of specific manual-based psychoeducation program for caregivers targeting at the needs of different groups.